Innovations in the Food System: Exploring the Future of Food - Clodoveo, Maria Lisa (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Innovations in Food Systems should be: Inclusive: ensuring economic and social inclusion for all food system actors, especially smallholders, women, and youth; Sustainable: minimizing negative environmental impacts, conserving scarce natural resources, and strengthening resiliency against future shocks; Efficient: producing adequate quantities of food for global needs while minimizing postharvest loss and consumer waste; Nutritious and healthy: enabling the consumption of a diverse range of healthy, nutritious, and safe foods. These are ambitious goals that will require multidisciplinary effort-from engineering to life sciences, biotechnology, medical sciences, social sciences, and economic sciences. New technologies and scientific discoveries are the solutions to the increasing demand for sufficient, safe, healthy, and sustainable foods influenced by the increased public awareness of their importance.